Efektivitas Jaminan Pemenuhan Hak-Hak Anak dan Perempuan Pasca Perceraian di Pengadilan Agama Sengkang Kelas 1 A - Makmur, Andi Dadi Mashuri; Novitasari; Sitti Amelia; Muh Bayu Aprilia Chandra; M Asraf Fradama (YP-SDI Lamaddukelleng, 2025)
This study aims to determine and evaluate the effectiveness of guarantees for the fulfillment of children's and women's rights after divorce in the Sengkang Class 1A Religious Court. The results of this study indicate that this type of research is an empirical legal research on the effectiveness of guarantees for the fulfillment of children's and women's rights after divorce in the Sengkang Class 1A Religious Court is less effective. Based on divorce cases that have permanent legal force but the fulfillment of children's and women's rights after divorce is not executed and in some cases the ex-husband does not have a fixed income or income, the inhibiting factors for the effectiveness of guarantees for the fulfillment of children's and women's rights after divorce in the Sengkang Class 1A Religious Court are legal compliance factors and financial capability factors. Of the two factors, the most influential factor is the financial capability factor.